2019
DOI: 10.5603/ep.a2018.0091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adipose tissue derived genes in endogenous Cushing’s syndrome versus diet-induced obesity

Abstract: Introduction: Dysregulation of adipokine secretion and action is a characteristic feature of obesity and a key clinical feature of Cushing's syndrome (CS). We have investigated whether endogenous glucocorticoid excess influences adipose tissue-derived gene expression. Material and methods: mRNA expression of adipokines; adiponectin, resistin, tumour necrosis factor-a, interleukin-6 (IL-6), angiotensinogen (AGT), plasminogen activator inhibitor type 1, retinol binding protein 4, visfatin, and cystatin C was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Resistin is one of the best-known adipocytokines. Over the years its blood concentrations have been tested, and its role in the pathogenesis of obesity, arterial hypertension, cardiovascular diseases, and stroke has been studied [16,17]. Qian et al [18] showed a higher concentration of this adipocytokine in the blood of obese mice.…”
Section: Resistinmentioning
confidence: 99%
“…Resistin is one of the best-known adipocytokines. Over the years its blood concentrations have been tested, and its role in the pathogenesis of obesity, arterial hypertension, cardiovascular diseases, and stroke has been studied [16,17]. Qian et al [18] showed a higher concentration of this adipocytokine in the blood of obese mice.…”
Section: Resistinmentioning
confidence: 99%
“…Patients with endogenous CS are typically exposed to high cortisol levels for longer period of time than the usual duration of laboratory experiments and interventional studies in humans, which suggests that CS could be an appropriate disease model in vivo that permits analysis of the influence of an excessive amount of GCs on the cardiovascular system and may potentially link it with GC-induced cardio-metabolic complications; thus, they could be adequately investigated. Moreover, it was reported that there were no major differences between endogenous hypercortisolism in Cushing's syndrome or diet-induced cardiometabolic disorders in terms of genetic cardiometabolic risk factors and regarding the pathogenesis of their complications [25]. We found that important "angioMIRs", both miRNA-126-3p and miRNA-126-5p, were significantly downregulated in PBNC circulating in CS patients, which, according to the literature, may indicate defective angiogenesis and reduced neovascularisation as miRNA-126 stimulates angiogenesis via VEGF signalling [26].…”
Section: Original Papermentioning
confidence: 99%